2022
DOI: 10.7326/m22-1329
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibodies for Treatment of SARS-CoV-2 Infection During Pregnancy

Abstract: Randomized controlled trials of monoclonal antibodies (mAbs) for the treatment of COVID-19 excluded pregnant persons. A retrospective, propensity score–matched, cohort study was conducted in a large health care system to examine the effect of several mAbs on hospitalization, obstetric-associated safety outcomes, and death during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
2
3
1
Order By: Relevance
“…In our series, a pregnant woman in active labor was also treated, and the study demonstrated a certain safety of monoclonal antibodies, such as not affecting breastfeeding in the first few days. These data are in agreement with previous data that showed the absence of serious treatment-related adverse events [ 10 , 35 , 36 , 37 ]. The low frequency of maternal–fetal adverse events may be explained by the younger age of the patients with few comorbidities and the exchanged maternal IgG between the mother and the newborn during the first few days after birth.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our series, a pregnant woman in active labor was also treated, and the study demonstrated a certain safety of monoclonal antibodies, such as not affecting breastfeeding in the first few days. These data are in agreement with previous data that showed the absence of serious treatment-related adverse events [ 10 , 35 , 36 , 37 ]. The low frequency of maternal–fetal adverse events may be explained by the younger age of the patients with few comorbidities and the exchanged maternal IgG between the mother and the newborn during the first few days after birth.…”
Section: Discussionsupporting
confidence: 93%
“…The first studies evaluating and reporting outcomes of pregnant women with COVID-19 and conducted with the combinations of Bamlanivimab/etesevimab and Casirivimab/imdevimab observed that monoclonal antibodies were well-tolerated and no adverse mother-fetus effects were reported [10,35,36]. Furthermore, another study similar to ours showed that adverse events after monoclonal antibody treatment were mild and rare [37]. However, neonatal outcomes have not been fully described due to a short follow-up period, while our study had a period of follow-up that was prolonged until 6 months.…”
Section: Discussionsupporting
confidence: 68%
“…The study demonstrated that adverse events after monoclonal antibody treatment were mild and rare. In addition, there was no difference in obstetric-related safety outcomes or COVID-19-related outcomes and non-COVID-19 related hospital admissions between the two arms [ 11 ]. Notably, neonatal outcomes were not fully described due to a short follow-up period.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…A large retrospective, propensity score-matched cohort study from the UPMC Health System insurance (Pittsburgh, PA, USA) from April 2021 to January 2022 included 994 women with a median gestational age of 179 days and mild to moderate COVID-19; 552 unvaccinated women received mAbs, and most were treated with sotrovimab; others received bamlanivimab and etesevimab or casirivimab and imdevimab [89]. Adverse events were rare, demonstrated in 1.4 % of women.…”
Section: Treatment With Monoclonal Antibodiesmentioning
confidence: 99%